Efficacy of bisulfite ions as an oxygen scavenger in monoethylene glycol (at least 20 wt%)/water mixtures - Salasi, Mobin; Pojtanabuntoeng, Kod; Wong, S.; Lehmann, M. (Society of Petroleum Engineers, 2017)
Copyright © 2017 Society of Petroleum Engineers. This study investigates the oxygen-scavenging behavior of bisulfite ions in monoethylene glycol (MEG)/water mixtures at concentrations commonly found in gas-transportation pipelines. Temperatures and pH values were varied. The influence of transition-metal (TM) ions to catalyze the bisulfite oxygen scavenging was studied. Experimental results indicate that MEG significantly inhibits bisulfite oxygen removal, which is hindered at low pH values and, to some extent, temperature. TMs can accelerate the oxygen-scavenging reaction in pH-unadjusted solutions, although the rate was still lower than that of the pH-adjusted solutions. The possible mechanism for such behavior and industrial implications are discussed.